(untitled) (Research, Society and Development, 2022)
Health hygiene habits are essential in any environment, especially in educational areas, where such habits should not only be practiced, but taught. Based on this fact, the research was carried out in a high school of reference, in a rural zone of Pernambuco, in order to identify and raise awareness of students’ habits regarding the use of individual items, in this case, cups. The study was divided into an educational intervention, in which they were instructed on the correct use of utensils and the risks of sharing it, and the assessment of changes in habits reported by students in the face of a structured questionnaire. Individual cups were also distributed, which the students themselves participated in the visual choice, aiming to encourage their use. Of the students who answered the questionnaire, 74.9% reported bringing the cups to school daily, furthermore, 75.2% would like the school to resume the distribution of plastic cups, justified by 53.7% believing that plastic waste are recycled, when in fact they are not. The students were open to the acceptance of new habits, however, it is necessary that such habits are accompanied by the knowledge and science that misuse can bring to collective health and the environment.